Las relaciones bilaterales entre Nicaragua y Ecuador: Situación actual y perspectivas a futuro - Tinajero Mullo, José Andrés Francisco (2014)
This job tries to establish in a general way the strategic axes of the bilateral relations between Nicaragua and Ecuador, which serve to determinate the perspectives and challenges for the future, based on a current diagnosis of the existing relations between the two countries. The objective is to develop a joint agenda of international cooperation South-South, that improves its strengths to the balanced development of their economies. Considering it, this job is divided into three parts: Start with the introductory part including the background to be considered to elaborate the strategic agenda, the justification of the research, conceptual framework, objectives, methodology and a diagnostic which contains Nicaragua’s general information. The second part contains an economic, social, and productive analysis which includes economic indicators that show the economic, social and political situation as well as the following matrixes: productive, energy and knowledge. Finally, the third part describes the international relations, geopolitics and a foreign policy agenda between Nicaragua and Ecuador. Additionally, it has been possible to establish some important axes that represent great opportunities to achieve a solid and prosperous international cooperation which are focused on the benefits that give the ALBA-TCP as an international organization of a regional order, to consolidate the regional integration and to promote de ambitious projects called “grannacionales”. It is also important, the construction of the Inter-Oceanic Canal of Nicaragua as a big project which contributes significantly to the region. The international cooperation for the development will be crucial in several sectors, such as: political, energetic, productive, educational, scientific and technological; as well as the strengthening existing cooperation and bilateral relations.